Exploring the role of antioxidants in sepsis-associated oxidative stress: a comprehensive review - Sahoo, Dipak Kumar; Wong, David; Patani, Anil; Paital, Biswaranjan; Yadav, Virendra Kumar; Patel, Ashish; Jergens, Albert E. (Frontiers in Cellular and Infection Microbiology, 2024)
Sepsis is a potentially fatal condition characterized by organ dysfunction caused by an imbalanced immune response to infection. Although an increased inflammatory response significantly contributes to the pathogenesis of sepsis, several molecular mechanisms underlying the progression of sepsis are associated with increased cellular reactive oxygen species (ROS) generation and exhausted antioxidant pathways. This review article provides a comprehensive overview of the involvement of ROS in the pathophysiology of sepsis and the potential application of antioxidants with antimicrobial properties as an adjunct to primary therapies (fluid and antibiotic therapies) against sepsis. This article delves into the advantages and disadvantages associated with the utilization of antioxidants in the therapeutic approach to sepsis, which has been explored in a variety of animal models and clinical trials. While the application of antioxidants has been suggested as a potential therapy to suppress the immune response in cases where an intensified inflammatory reaction occurs, the use of multiple antioxidant agents can be beneficial as they can act additively or synergistically on different pathways, thereby enhancing the antioxidant defense. Furthermore, the utilization of immunoadjuvant therapy, specifically in septic patients displaying immunosuppressive tendencies, represents a promising advancement in sepsis therapy.